Behavior of partially concrete-filled X-joints with CHS braces and SHS chord under axial compression. (September 2021) - Guo, Zhan; Li, Chengkai; Zhu, Qingxia; Chen, Yu
Abstract: The paper experimentally studies the static behavior of partially concrete-filled X-joints with circular hollow section (CHS) braces and square hollow section (SHS) chord under axial compression. Totally 40 partially concrete-filled CHS-SHS X-joints were designed, including 20 X-joints with concrete-filled CHS braces and hollow SHS chord (CFCHS-SHS) and 20 X-joints with hollow CHS braces and concrete-filled SHS chord (CHS-CFSHS). The impacts of the brace diameter to chord width ratio ( β = d / b ) and chord width to double chord thickness ratio ( γ = b /2 T ) on the static behavior of CHS-SHS X-joints were experimentally studied. At the same time, the corresponding finite element analysis (FEA) models were established and validated by comparison with test results, and then an extensive parametric investigation was performed to study the effects of three main influential factors ( τ, concrete filling position, and in-filled concrete strength) on the ultimate strength of CHS-SHS X-joints under axial compression. The test results show that the CFCHS-SHS X-joints and CHS-CFSHS X-joints exhibit completely different failure modes under axial compression. All CFCHS-SHS X-joints are failed with chord plasticization, while the local buckling of the brace members is the primary failure mode for the CHS-CFSHS X-joints. The ultimate strength and axial stiffness of CHS-CFSHS X-joints are significantly higher than those of CFCHS-SHS X-joints. However, the ductility of CHS-CFSHS X-joints is slightly superior to that of CFCHS-SHS X-joints. Based on the analyses of test results, the design equations derived from the simplified yield line model were put forward for the estimation of the ultimate strength of CFCHS-SHS X-joints, which was verified to be reasonable and accurate. In addition, the study also revealed that the total cross-section yield strength of the brace could be utilized to accurately predict the ultimate strength of CHS-CFSHS X-joints. Graphical abstract: Unlabelled Image Highlights: The CFCHS-SHS X-joints and CHS-CFSHS X-joints exhibit different failure modes under axial compression. The ultimate strength and axial stiffness of CHS-CFSHS X-joints are higher than those of CFCHS-SHS X-joints. The corresponding finite element analysis (FEA) models were established and validated by comparison with test results. The design equations derived from simplified yield line models were presented for CFCHS-SHS X-joints.